Participação do receptor do fator de ativação plaquetária nas alterações metabólicas e na secreção de Citocinas em animais com aumento de adiposidade. - Zelia Menezes (2010)
Recent studies have demonstrated the participation of several inflammatory mediators in immune and metabolic changes resulting from increased adiposity. This study evaluated the participation of the platelet-activating factor (PAF) receptor in the metabolic changes inadipose tissue through the use of animals with genetic deletion for this receptor. The animals were divided into four groups: wild type fed control diet (WT-C), wild type fed palatable diet (WT-P), animals with PAF receptor deletion fed a control (PAFR-/--C) or palatable diet (PAFR-/--P).The group WT-P showed increased adiposity, adipocyte hypertrophy, increased acetyl-CoA carboxylase (ACC) and lipoprotein lipase (LPL) enzymes expression, increased total cholesterol serum concentration and high levels of the adipose tissue cytokines IL -1B, Il-10, CCL3 and CCL5.The mice fed a palatable diet also showed lower glucose oraltolerance. The group PAFR-/--P showed increased body weight gain, exacerbated visceral adipose tissues fat mass, associated with hypertrophy of adipocytes when compared with group PAFR-/--C and WT-P. The group PAFR-/--P also had increased triglyceride and totalcholesterol serum levels. No change was observed in relation to adipose tissue cytokines concentration or oral glucose tolerance in relation PAFR-/--C animals. The adipocyte lipolysis was lower in PAFR-/--C, as well as, the release of TNFa and IL-6 cytokines , both in basal orhyperglycemic medium conditions, when compared to WT-C group.The results suggest that the presence of PAF receptor is important for the negative control of adiposity, for lipid homeostasis and the increased cytokines concentration in epididymal adipose tissue. The high levels of adipose tissue cytokines appears to be important to control the fat mass expansion. The increased adiposity observed in the absence of the PAFreceptor can also, at least in part, be due to the lower adipocyte lipolysis.